Empowerment of Hypertension Awareness Group as An Effort to Control Blood Pressure in Rancamanyar, Bandung District - Riandi Alfin; Anggriyana TW; Lulu Fauziah; Tri Julianto (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Hypertension is one of the most common diseases found in society. Hypertension can occur because there is a wrong lifestyle that a person has lived before. Uncontrolled blood pressure can make the condition worse and lead to fatal complications and even death. Efforts can be made to improve the health status of the community in the sub-district, Bandung Regency by providing health services at the community level. The implementation of empowering hypertension care groups is expected to increase knowledge, attitudes and treatment related to hypertension. The implementation of this community service uses a community-based educational programme approach with the formation of community groups that care about hypertension in the sub-district, Bandung district. The research method used in this community service activity uses one group pre post design methodology with consecutive sampling technique. In addition, this activity aims to form hypertension care groups within cadres and community leaders who are measured for knowledge and attitudes before and after receiving hypertension health education. The results of this community service activity are significant differences in knowledge about hypertension (P Value 0.001) and attitudes about hypertension (P Value 0.001) in hypertension care groups about hypertension before and after participating in this community service activity (P Value <0, 05). Through this community service, a hypertension care group was formed consisting of health cadres and residents of the sub-district, Bandung district itself. This hypertension care group has a programme related to health improvement and can take blood pressure measurements independently. Through the formation of community-based hypertension care groups, it is hoped that this activity can be applied independently by the community through programmes from community groups that can have an impact on improving the health status of the community in the District, Bandung Regency.